A Review of Therapeutic Aptamer Conjugates with Emphasis on New Approaches - John G. Bruno (MDPI AG, 2013)
The potential to emulate or enhance antibodies with nucleic acid aptamers while lowering costs has prompted development of new aptamer-protein, siRNA, drug, and nanoparticle conjugates. Specific focal points of this review discuss DNA aptamers covalently bound at their 3' ends to various proteins for enhanced stability and greater pharmacokinetic lifetimes in vivo. The proteins can include Fc tails of IgG for opsonization, and the first component of complement (C1q) to trigger complement-mediated lysis of antibiotic-resistant Gram negative bacteria, cancer cells and possibly some parasites during vulnerable stages. In addition, the 3' protein adduct may be a biotoxin, enzyme, or may simply be human serum albumin (HSA) or a drug known to bind HSA, thereby retarding kidney and other organ clearance and inhibiting serum exonucleases. In this review, the author summarizes existing therapeutic aptamer conjugate categories and describes his patented concept for PCR-based amplification of double-stranded aptamers followed by covalent attachment of proteins or other agents to the chemically vulnerable overhanging 3' adenine added by Taq polymerase. PCR amplification of aptamers could dramatically lower the current $2,000/gram cost of parallel chemical oligonucleotide synthesis, thereby enabling mass production of aptamer-3'-protein or drug conjugates to better compete against expensive humanized monoclonal antibodies.